The Choline/Ethanolamine Kinase Family in Arabidopsis: Essential Role of CEK4 in Phospholipid Biosynthesis and Embryo Development. Issue 5 (12th May 2015) - Lin, Ying-Chen; Liu, Yu-chi; Nakamura, Yuki
Abstract : Arabidopsis CEK4 may be the plasma membrane-localized isoform of the choline/ethanolamine kinase family involved in the rate-limiting step of phosphatidylcholine biosynthesis and embryo development. Abstract: Phospholipids are highly conserved and essential components of biological membranes. The major phospholipids, phosphatidylethanolamine and phosphatidylcholine (PtdCho ), are synthesized by the transfer of the phosphoethanolamine or phosphocholine polar head group, respectively, to the diacylglycerol backbone. The metabolism of the polar head group characterizing each phospholipid class is poorly understood; thus, the biosynthetic pathway of major phospholipids remains elusive in Arabidopsis thaliana . The choline/ethanolamine kinase (CEK ) family catalyzes the initial steps of phospholipid biosynthesis. Here, we analyzed the function of the four CEK family members present in Arabidopsis. Knocking out of CEK4 resulted in defective embryo development, which was complemented by transformation of genomic CEK4 . Reciprocal genetic crossing suggested that CEK4 knockout causes embryonic lethality, and microscopy analysis of the aborted embryos revealed developmental arrest after the heart stage, with no defect being found in the pollen. CEK4 is preferentially expressed in the vasculature, organ boundaries, and mature embryos, and CEK4 was mainly localized to the plasma membrane. Overexpression of CEK4 in wild-type Arabidopsis increased the levels of PtdCho in seedlings and mature siliques and of major membrane lipids in seedlings and triacylglycerol in mature siliques. CEK4 may be the plasma membrane-localized isoform of the CEK family involved in the rate-limiting step of PtdCho biosynthesis and appears to be required for embryo development in Arabidopsis.